VARIASI BAHASA BALI DIALEK KUTA SELATAN (KAJIAN SOSIODIALEKTOLOGI) - Putu Devi Maharani; Komang Dian Puspita Candra (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2017)
ABSTRACT Balinese language is a traditional language spoken by the local people of Bali. In use, there are variations that have specific characteristics in each region. Differences or variations in the use of Balinese language can be observed in each district at the level of sound, morphological, syntactic and lexical. The variation in Balinese language raises particular dialect in each region. Accordingly, this study specifically addresses the lexical and sounds or phonological variation contained in the dialect of Balinese Language, specifically in the area of Jimbaran, Kedonganan and Unggasan and also found the factors contributing those variations happened. Sociolinguistics, Dialectology and Phonology Generative approaches were applied in the analysis of this research.The method of collecting the data in this research are close observation method with refers to the technique of tapping, face-to-face interview technique, eave-dropping technique, recording and note-taking technique.Generally found there are some lexical variation found in these three areas used to mention the same things. The lexical variation found are in class of pronoun, noun, verb, adjective, and adverbial. In phonological variation found there are 7 variations in Jimbaran, 5 variations in Kedonganan, and 7 variations in Ungasan. Those phonological variations also analyzed phonological rules to find out in what environment some sound of morpheme will change in each dialect.